Responsibilities of Witness and Victim Protection Institutions in Legal Protectionof Whistle Blower and Justice Collaborator - Pratama, Putri; Hasuri (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2025)
The role of the Witness and Victim Protection Agency (LPSK) in ensuring the safety of whistleblowers and justice collaborators is very important in the criminal justice system in Indonesia. Whistleblowers and justice collaborators often face serious threats, both to their physical and psychological safety, so effective protection is an important prerequisite for encouraging their participation in uncovering crimes, especially major crimes such as corruption and terrorism. This study uses a qualitative method with an empirical juridical approach, the primary data source comes from the Witness and Victim Protection Institute (LPSK) while the secondary data comes from books, journals, encyclopedias, dictionaries, and virtual sources. while data management techniques through analytical descriptive, The results of this study show the responsibility of the Witness and Victim Protection Institute (LPSK) towards witnesses and victims and the legal position of whistle blowers and justice collaborators towards the criminal justice system.